2021
DOI: 10.3390/s21072281
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term IoT-Based Maternal Monitoring: System Design and Evaluation

Abstract: Pregnancy is a unique time when many mothers gain awareness of their lifestyle and its impacts on the fetus. High-quality care during pregnancy is needed to identify possible complications early and ensure the mother’s and her unborn baby’s health and well-being. Different studies have thus far proposed maternal health monitoring systems. However, they are designed for a specific health problem or are limited to questionnaires and short-term data collection methods. Moreover, the requirements and challenges ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 79 publications
1
34
0
Order By: Relevance
“…In this study, we continuously collected HRV data from pregnant women using an IoT-based maternal monitoring system [ 26 ]. The system could collect a considerable amount of HRV data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we continuously collected HRV data from pregnant women using an IoT-based maternal monitoring system [ 26 ]. The system could collect a considerable amount of HRV data.…”
Section: Discussionmentioning
confidence: 99%
“…The collected data were transferred to the cloud server for further analysis. The use of such a home-based system during pregnancy and postpartum period was evaluated in a previous study [ 26 ]. The findings of this pilot study indicated the feasibility of the study, robustness of the system, and reliability of the collected HRV parameters.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The various scientific applications apart from image analysis, text recognition and language processing include health care applications like drug activity designing, prediction of risk and gene mutation expression, medical outcomes, propose management in diabetes and mental health, and predict the progression of congestive heart failure, cardiac arrhythmia, bone disease, Alzheimer disease and benign and malignant tumor. 11 , 12 , 13 , 14 , 15 , 16 …”
Section: How Iomt Work!mentioning
confidence: 99%
“…Recently, several PPG-based wearable devices have been proposed for health parameters monitoring in everyday life settings. Several studies leveraged different wearable devices, such as Samsung Gear Sport, Apple Watch, Fitbit, and Garmin Vivosmart, for health monitoring in different population-based groups [12][13][14]. With advancements in technology, it is expected that the use of such wearable devices will grow further as they become smaller and lighter with longer battery life.…”
Section: Introductionmentioning
confidence: 99%